ADSDPP as roadmap to sustainable future of IP communities - Abansi, Corazon L. (Cordillera Review : Journal of Philippine Culture and Society, 2011)
The Ancestral Domain Sustainable Development and Protection Plan (ADSPP) is the consolidation of the plans of indigenous cultural communities (ICCs) within an ancestral domain for the sustainable management and development of their land and natural resources as well as the development of human and cultural resources based on their indigenous knowledge systems and practices. The ADSDPPs formulated by the communities and facilitated by the National Commission on Indigenous Peoples (NCIP) were assessed in terms of the extent to which each plan supports the four-fold rights of indigenous peoples (IPs); the effectiveness of the plan in terms of its responsiveness to the needs of the community; and the efficiency of the plan as manifested by the appropriate match between community assets and programs. The results highlight the centrality of land rights to the restoration of security of indigenous peoples. In anchoring the plans on the four-fold bundles of rights, resource management decisions are made more accountable to critical human values, ecological sustainability, economic equity, and cultural diversity. The parallel targets of effectiveness and efficiency in formulation of plans will continue to be a work-in-progress among ICCs. The imperatives of a continuing capability-building program for local NCIP workers in assisting ICCs develop their ADSDPPs cannot be overlooked. Likewise, an intervention in the preparation and implementation of the ADSDPP will not be strategic and complete without the capacity development of IP leaders. Mainstreaming of the ADSDPP into arenas at different levels such as government and like-minded agencies and groups and targeting appropriate message routes will make the ADSDPP a living document for the IPs.